Functional specialisation of GABAergic cells in the basolateral amygdala - Bienvenu, T (2011)
The amygdala, in particular its basolateral part (BLA), plays a critical role in binding affective qualities to otherwise neutral stimuli, and in eliciting emotional behaviors. Plasticity of inputs to BLA projection neurons involved in emotional memory has been extensively studied. However, how BLA neurons collectively process sensory information to encode and stabilize emotional memories is unknown. Precise coordination of BLA network activities seems critical. Specifically, timed integration of salient stimuli, and synchrony with hippocampal theta oscillations appear to be important. Recent reports suggest that GABAergic neurons may be instrumental in shaping ensemble activity in the BLA. Studies of neocortex and hippocampus showed that diverse GABAergic interneuron types play highly specific roles in coordinating network operations. The presence of similar interneuron populations in the BLA suggests comparable mechanism may govern its activities. However, GABAergic cell types and their functions have not been characterized. In this thesis, I tested the hypothesis that GABAergic neurons innervating the BLA contribute to noxious stimulus integration and are engaged in hippocampal-amygdala synchrony in a type-dependent manner. I combined the analysis of in vivo firing of BLA neurons with their post hoc anatomical characterization. Local field potentials were recorded in dorsal hippocampus simultaneously with unit activity in the BLA of urethane-anesthetized rats. Hindpaw pinches and electrical footshocks were used as noxious stimuli. After recording, neurons were filled with Neurobiotin using juxtacellular labeling. Cells were identified on the basis of their axonal and dendritic patterns, neurochemical contents and postsynaptic targets, using light and electron microscopy. Five types of GABAergic neurons innervating distinct targets in the BLA were unambiguously characterized. Their firing was differently coupled to hippocampal theta oscillations and noxious stimuli. This work provides a first evidence of GABAergic cell type-specific roles in coordinating BLA activities. In addition, I show that amygdala and cortical activities follow distinct rules. The cooperative actions of GABAergic neurons in the BLA may ensure timed integration of salient stimuli and ongoing brain oscillations, thereby contribute to form precise and stable emotional memories.